The Trade Effects of Border Controls: Evidence from the European Schengen Agreement - Gabriel Felbermayr; Jasmin Gröschl; Thomas Steinwachs (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2016)
The Schengen agreement has guaranteed unchecked travel across internal EUborders since 1995. Has it also facilitated trade flows? Our econometric analysissuggests that Schengen has boosted trade by 3% on average (equivalent to a drop in tariffs by 0.7 percentage points). Goods trade is more robustly affected than services, and peripheral countries benefit more than central ones.
Keywords: F10; F15; N74; N94; 330; Trade Integration; Schengen Agreement; Gravity